Takaful simplified pertinent FAQ for quick reference and understanding - Saiful Yazan Ahmad (Penerbit Universiti Utara Malaysia, 2017)
This book aims to answer some key questions are often raised about the takaful business based on current market practice and as a quick reference source for anyone interested.